Cognitive Misperception and Chronic Disease Awareness: Evidence from Blood Biomarker Data - Zhuoer Lin; Mingqi Fu; Xi Chen (Global Labor Organization (GLO), 2023)
Cognitive misperception contributed to poor decision-making; yet their impact on health-related decisions is less known. We examined how self-perceived memory was associated with chronic disease awareness among older Chinese adults. Data were obtained from the China Health and Retirement Longitudinal Study. Nationally representative blood biomarkers identify participants' dyslipidemia and diabetes status. Among participants with biomarker identified dyslipidemia or diabetes, disease awareness was defined as self-reported diagnosis of the conditions. The proportions of disease awareness were lower for individuals with better self-perceived memory and those with more impaired cognitive ability, showing opposite patterns. Controlling for cognitive ability and covariates, self-perceived memory was negatively associated with the dyslipidemia and diabetes awareness. In particular, older adults with the highest level of self-perceived memory had significantly lower disease awareness as compared to those with the lowest level of self-perceived memory. Our findings were robust to alternative cognitive measures and were stronger for less educated rural residents or those living without children. Cognitive misperception poses great challenges to chronic disease management. Targeted interventions and supports are needed, particularly for the disadvantaged.
Keywords: I12; J14; D91; I18; 330; Cognitive impairment; Self-perceived memory; Chronic disease awareness; Dyslipidemia; Diabetes